Nutritional Status and its Related Factors in Older People Residing in Nursing Homes in Semnan Province, Iran, 2017 - Tahereh Dehdari; Mehri Delvarianzadeh; Nahid Ariaeean; Farideh Khosravi; Aysa Bahar (University of Social Welfare & Rehabilitation Sciences, 2019)
Objectives: Older people are a vulnerable group that their undesirable nutritional status makes them susceptible to catch diseases and increase their health costs. This study was conducted to determine the nutritional status of older people in nursing homes of Shahroud and Damghan cities (Semnan Province) and some influential factors in 2017. Methods & Materials: This cross-sectional study (analytical descriptive type) was carried out in nursing homes of Shahroud and Damghan cities using census sampling method. By using a demographic questionnaire, minimal nutrition assessment, and anthropometric evaluation by the researcher, the data of 129 older people were collected. Then the obtained data were analyzed by the Chi-square, 1-way ANOVA, and Independent t-test in SPSS. The significance level was set at 0.05. Results: The Mean±SD age of the participants was 75.44±10.56 years. In terms of nutritional status, (22.5%) of the subjects had malnutrition, (57.4%) malnutrition risk, and (20.2%) a good nutritional status. There was a statistically significant relationship between the nutritional status and variables of sex and age, income, smoking, body mass index, arthritis, urinary problems, and using mass media (P<0.05).  Conclusion: The nutritional status of a few participants was desirable. So, today's older people nutritional status is far from acceptable standards and requires planning and serious consideration of relevant organizations, especially the health system.